Beautiful and Beautiful Enough: A Survey based Research Into the 21st Century Understanding and Use of Cosmetics - Priya Noble, ANN; K. , Devi (International Journal of Psychosocial Rehabilitation, 2020)
The use of cosmetics has been in place since time immemorial, and the existing archaeological evidence proves the prevalence of cosmetic products in practices such as bathing in scented oil in order to protect and smoothen one’s body or chewing herbs to be devoid of bad breath in ancient civilizations. However, through the ages, the understanding of the application of cosmetic products, especially facial cosmetics, has drastically taken a reverse wind. It started gaining political and classist meanings through the rise of a totalitarian and capitalist rule around the world. With a striking rise in the readership of women’s magazines, media took up the responsibility of propagating the patriarchal framework of a perfect body. The invention of moving pictures also offered people an idea to base themselves on and compare. But through the ages, these understandings of the use of cosmetics have been deconstructed by people, especially women, to revoke it as a platform for expression and creativity. Nevertheless, the business mindset and the consumerist mentality in people have brought a sheer change in the marketing and promotion of cosmetic products, unlike the wave of this nouveau thought. This paper, titled ‘Beautiful and Beautiful Enough: A Survey-Based Research into the 21st Century Understanding and Use of Cosmetics, is based upon the responses that we received from fifty people of diverse geographical areas and cultures and examines this change in the thought and practice of using cosmetics. It also discusses the marketing practices of the beauty industry, exploitation, psychosocial development, and trauma experienced behind the propagation of a ‘better other.’